Service quality and students' satisfaction toward the Academic Affairs Division Services: UiTM Sarawak students' perspectives / Mohd Hazizol Haji Sidi Ahmad - Haji Sidi Ahmad, Mohd Hazizol (Faculty of Business and Management, Universiti Teknologi MARA, 2015)
Service quality is a concept that has aroused considerable interest and debate in the research literature because of the difficulties in both defining and measuring it with no overall consensus emerging on either. Students'satisfaction and service quality are often .treated together as functions of students' perception and expectation and research has shown that high service quality contribute significantly to profitability. Service quality is required to be first measured in order to improve the quality in a service organization. Practitioners and academics are eager on measuring service quality accurately in order to have better understanding of its indispensable antecedent and consequences, and eventually ascertain methods for improving and measuring service quality in search for competitive advantage. This paper aims to investigate how students perceive the service quality offered by the administrative staff of the academic affairs department at UiTM Sarawak. The questionnaires were distributed among the students at UiTM Sarawak, Samarahan campus. The measurements used were based on the widely accepted SERVQUAL model which is the most common method for measuring service quality. A descriptive statistics analysis was used to assess the students' perception on the quality of services provided by the administrative staff of the UiTM Academic Affairs Division. This study also identifies the diploma and bachelor degree students' satisfaction towards the overall service quality provided. The results of the study indicated that all of the service quality dimensions are important. The tangibles dimension is the most satisfied dimensions from the respondent's point of view among the others and respondents are less satisfied with the reliability dimension especially the staff provided services at the promised time. Besides that, tangible was rated as the most important SERVQUAL dimension followed by assurance, responsiveness, empathy and reliability. Other than that, the diploma students were more satisfied to the overall service quality compare to the bachelor degree students.